The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3109/14767058.2014.947577
|View full text |Cite
|
Sign up to set email alerts
|

Influence of threatened miscarriage on pregnancy and early postpartum period: a case–control report

Abstract: Increased complications after threatened miscarriage is probably due to the persistence of a triggering mechanism. As preterm birth and abortion rate increased, whilst uterine atony rate decreased, one of the mechanisms causing threatened miscarriage might be increased uterine contractility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
5
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 12 publications
4
5
1
2
Order By: Relevance
“…Although we detected abruptio placentae more frequently in the group of patients with the risk of miscarriage than in the control group (OR 95% CI 2.99), no significant difference was detected. Our abruptio placenta results are like many previous studies [9,11,18,23,24]. However, there are also publications linking abruptio placentae with the risk of miscarriage [19].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Although we detected abruptio placentae more frequently in the group of patients with the risk of miscarriage than in the control group (OR 95% CI 2.99), no significant difference was detected. Our abruptio placenta results are like many previous studies [9,11,18,23,24]. However, there are also publications linking abruptio placentae with the risk of miscarriage [19].…”
Section: Discussionsupporting
confidence: 88%
“…Weiss et al have shown that there may be an increase in the incidence of preeclampsia, which is a serious complication, in pregnancies with the risk of miscarriage [11]. Conversely, in our study, and in many instances in the literature there was no relationship between preeclampsia and the risk of miscarriage [7,9,19,23]. In our study, placenta previa was more frequent in the patients with the risk of miscarriage in the first trimester than in the control group.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…Поліморфізм гена рецептора прогестерону визначає різну активність рецепторної функції. У свою чергу, різна активність рецептора сприяє зміні чутливості до ендогенного та екзогенного прогестерону [5].…”
unclassified